Drag Queen: uma potência transgressora - Brasil, Iran Almeida (2017)
This dissertation proposes to think the figure of drag queen in another scenario (in the field of education) realizing the infinite possibilities in addition to the arts, (un)building established between content and form, reinventing new forms of interaction, of knowing and knowledge. The intent of questioning of these possibilities is given through this figure always, which manufactures moving your own beauty, not being taken as a product and as a figure, drag does not follow standards, it creates its own. The encounter with this figure crossed by intensities that move, creating interconnections from a body in the process of doing art. The body/figure of drag who stars in actions and at the same time think about them in order to create new forms of interaction between subjects. To get to the cable research on drag, here was the auto-ethnography. For Daniela Versiani (2005), the construction of the auto-ethnography research takes place in the auto-reflection of the subject/artist and in this experience, the moves, what affects, what makes you think. When you think of the figure of the drag queen as a poetic figure I've been inspired in the philosopher Friedrich Nietzsche (2011) and your concept of will to power. It adds the set of references that don't only affect my practice as well as performativity, such as pedagogical movies Priscilla, Queen of the desert; To Wong Foo, Thanks for Everything! Julie Newmar; and the documentary Pageant; these materials which make me weave relationships and questioning as subject/drag/professor that I'm this way, the figure of drag queen invites thinking the subject/character in daily life, in your teaching and practice, and can be exploited under other settings.